The presence of Kierkegaard in Vernunft und Existenz by Karl Jaspers - Dip, Patricia C. (Anales del Seminario de Historia de la Filosofía, 2026)
From the outbreak of the First World War until Hitler’s rise to power, Jaspers develops his philosophy within the framework of a process that begins in 1913 with the publication of General Psychopathology, continues with the publication of Psychology of Worldviews (1919) and finally takes shape in Philosophy (1932). A year earlier, in The Spiritual Situation of the Age, Kierkegaard and Nietzsche, as in Reason and Existence (1935), are presented as exceptional thinkers worthy of attention. In this work, Jaspers presents a philosophy that attempts to establish a balance between the rational and the existential poles. Presas is concerned with evidencing the Kantian basis of Jaspers’ theoretical project as far as the rational pole is concerned. We believe that the existential pole is determined by Kierkegaard’s thought. The aim of this paper is to show how the ideas of the Danish thinker are used to achieve the balance sought in the formulation of Karl Jaspers’ own Philosophy of existence during the 1930s.